Aluminum Poisoning with Emphasis on Its Mechanism and Treatment of Intoxication - Mehrdad Rafati Rahimzadeh; Mehravar Rafati Rahimzadeh; Sohrab Kazemi; Roghayeh Jafarian Amiri; Marzieh Pirzadeh; Ali Akbar Moghadamnia (Emergency Medicine International)
Aluminum poisoning has been reported in some parts of the world. It is one of the global health problems that affect many organs. Aluminum is widely used daily by humans and industries. Residues of aluminum compounds can be found in drinking water, food, air, medicine, deodorants, cosmetics, packaging, many appliances and equipment, buildings, transportation industries, and aerospace engineering. Exposure to high levels of aluminum compounds leads to aluminum poisoning. Aluminum poisoning has complex and multidimensional effects, such as disruption or inhibition of enzymes activities, changing protein synthesis, nucleic acid function, and cell membrane permeability, preventing DNA repair, altering the stability of DNA organization, inhibition of the protein phosphatase 2A (PP2A) activity, increasing reactive oxygen species (ROS) production, inducing oxidative stress, decreasing activity of antioxidant enzymes, altering cellular iron homeostasis, and changing NF-kB, p53, and JNK pathway leading to apoptosis. Aluminum poisoning can affect blood content, musculoskeletal system, kidney, liver, and respiratory and nervous system, and the extent of poisoning can be diagnosed by assaying aluminum compounds in blood, urine, hair, nails, and sweat. Chelator agents such as deferoxamine (DFO) are used in the case of aluminum poisoning. Besides, combination therapies are recommended.